(untitled) (International Journal of Medical and Surgical Sciences, 2014)
Early ductal decompression in the treatment of acute biliary pancreatitis with ampullary obstruction is controversial. The objective of this study is to determine the methodological quality, internal and external validity of the article of Acosta et al. (2006), which compares the effectiveness of early ductal decompression versus conservative management in acute biliary pancreatitis with ampullary obstruction. Acosta et al. (2006), article was subjected to a therapy User’s Guide. Subsequently its methodological quality was analyzed applying 3 instruments; MINCIR therapy, CONSORT and SIGN. The application of these instruments was performed independently by four researchers, trained in critical analysis of the literature and clinical epidemiology. The article is not oriented to a definite question. It has a random assignment of participants, but these were not properly considered until the end of the study. It has 16 points of MINCIR scale (cut-off of the methodological quality construct is 18). It complies with only 10 of the 21 items of CONSORT. All instruments used put into evidence similar methodological weaknesses that lead to questioning of the internal and external validity of the study, a fact that in turn questions the logic of the applicability of this protocol.